2013
DOI: 10.1371/journal.pone.0060334
|View full text |Cite
|
Sign up to set email alerts
|

Screening Compounds with a Novel High-Throughput ABCB1-Mediated Efflux Assay Identifies Drugs with Known Therapeutic Targets at Risk for Multidrug Resistance Interference

Abstract: ABCB1, also known as P-glycoprotein (P-gp) or multidrug resistance protein 1 (MDR1), is a membrane-associated multidrug transporter of the ATP-binding cassette (ABC) transporter family. It is one of the most widely studied transporters that enable cancer cells to develop drug resistance. Reliable high-throughput assays that can identify compounds that interact with ABCB1 are crucial for developing new therapeutic drugs. A high-throughput assay for measuring ABCB1-mediated calcein AM efflux was developed using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 46 publications
(51 reference statements)
1
41
0
Order By: Relevance
“…Our data suggest a calcein-AM trapping effect that only becomes apparent when the calcein-AM efflux pump, MRP-1, is sufficiently inhibited. This effect seems at odds with the currently held belief that calcein-AM rapidly diffuses across the cell membrane25. Passive diffusion down its concentration gradient would imply that calcein-AM diffuses out of the cell at a similar rate as that with which it is taken up after extracellular calcein-AM is removed.…”
Section: Discussionmentioning
confidence: 89%
“…Our data suggest a calcein-AM trapping effect that only becomes apparent when the calcein-AM efflux pump, MRP-1, is sufficiently inhibited. This effect seems at odds with the currently held belief that calcein-AM rapidly diffuses across the cell membrane25. Passive diffusion down its concentration gradient would imply that calcein-AM diffuses out of the cell at a similar rate as that with which it is taken up after extracellular calcein-AM is removed.…”
Section: Discussionmentioning
confidence: 89%
“…Therefore, Calcein efflux assay is considered a functional indicator of MDR activity. 5557 We observed that the encapsulated MCF-7R cells could be divided into three distinct subtypes based on high, medium and minimal levels of Calcein AM fluorescence (Fig. 4A).…”
Section: Resultsmentioning
confidence: 94%
“…In contrast, BI 2536 appeared not to interact with ABCC1 at all. Interestingly, in a recent study aimed to develop a novel high-throughput assay identifying ABCB1 interacting compounds, BI 2536 was identified as a positive hit from a library 193 compounds [44]. Next, we measured the effect of BI 2536 on the vanadate-sensitive ATPase activity of ABCB1 and ABCG2 (Fig.…”
Section: Discussionmentioning
confidence: 99%